Ketotifen and nocturnal asthma. - Catterall, J R (1983)
Patients with asthma often wheeze at night and they also become hypoxic during sleep. To determine whether ketotifen, a drug with sedative properties, is safe for use at night in patients with asthma, we performed a double blind crossover study comparing the effects of a single 1 mg dose of ketotifen and of placebo on arterial oxygen saturation (SaO2), breathing patterns, electroencephalographic (EEG) sleep stage, and overnight change in FEV1 in 10 patients with stable asthma. After taking ketotifen, the patients slept longer and their sleep was less disturbed than after taking placebo, true sleep occupying 387 (SEM 8) minutes after ketotifen and 336 (19) minutes after placebo (p less than 0.02). On ketotifen nights the patients had less wakefulness and drowsiness (EEG sleep stages 0 and 1) and more non-rapid eye movement (non-REM) sleep than on placebo nights, but the duration of REM sleep was similar on the two occasions. Nocturnal changes in SaO2, the duration of irregular breathing, and overnight change in FEV1 were unaffected by ketotifen.